Laterais do Português Europeu Contemporâneo: estruturação interna, robustez de traços e dados de aquisição - Amorim, Clara; Veloso, João (Revista da Associação Portuguesa de Linguística, 2021)
This work intends to discuss the distinctive features of the laterals in Contemporary European Portuguese, in particular the features [+lateral] and [+continuous], based on language acquisition data. For this purpose, the productions of 80 typically developing children aged between 3 and 4 years and eleven months were analyzed. The results show that, after the nasals, the lateral in onset position is the first sonorant to be acquired. If the laterals are distinguished from the rhotics by the marked feature [+lateral], it would be expected that the class of the rhotics would be acquired before the laterals, since the acquisition of segments is made by the gradual acquisition of marked features and by their combination with features already acquired. The fact that /l/ is acquired before the rhotics suggests that the feature [+lateral] is not responsible for establishing the contrast between the two classes. Based on the data analyzed, the feature [+approximant] is proposed to characterize the laterals and rhotics, distinguishing them from the other sonorants, and the feature [[±continuant] to differentiate the rhotics from the laterals, the latter being characterized by the negative value of this feature.